Pengembangan Sekolah Berbasis Go Green dan Waste Management untuk Mewujudkan Green School di SDI Miftahul Huda Plosokandang Kabupaten Tulungagung - Chusnul Chotimah (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2019)
In supporting the environmental conservation program, protecting the earth from damage caused by human activities and unfriendly activities, it is necessary to instill early education about preserving the environment and conservating the earth free of garbage while reducing the impact of global warming. SDI Miftahul Huda Plosokandang Tulungagung care about it. This issue are green school and waste management was carried out the empowerment of educational institution. This study uses the Community Based Research (CBR) method with the Asset-Based Approach (ABA) to empower schools to achieve green school and waste management. The results achieved by the school are able to integrate environmental awareness in the curriculum, create healthy living habits and using of a green environment based on green schools and waste management.